Unknown primary head and neck squamous cell carcinoma in the era of fluorodeoxyglucose‐positron emission tomography/CT and intensity‐modulated radiotherapy. Issue 7 (28th March 2017) - de Ridder, Mischa; Klop, Martin; Hamming‐Vrieze, Olga; de Boer, JanPaul; Jasperse, Bas; Smit, Laura; Vogel, Wouter; van den Brekel, Michiel; Al‐Mamgani, Abrahim
Abstract: Background: The diagnosis and treatment of head and neck carcinoma of unknown primary (CUP) have changed with the introduction of fluorodeoxyglucose‐positron emission tomography (FDG‐PET)/CT and intensity‐modulated radiotherapy (IMRT), with potential implications for outcome. Methods: We conducted a retrospective analysis of 80 patients with head and neck CUP who were PET‐staged and treated with curative intention using IMRT between 2006 and 2016 in the Netherlands Cancer Institute. Patient, tumor, and treatment demographics were recorded and oncologic outcomes were analyzed. Results: Local control was 100% in mucosal irradiated patients. Regional control was 90%. Ten patients developed distant metastases, which were associated with N3, extracapsular extension (ECE) and lower neck positive lymph nodes. Overall survival (OS) at 5 years was 62% and disease‐specific survival was 78%. ECE, N3 neck, multiple levels of positive lymph nodes, and positive lymph nodes in the lower neck were associated with worse prognosis. Conclusion: Locoregional outcome of head and neck CUP managed with modern techniques is good. Future research needs to focus on reducing toxicity and patients prone for distant metastasis.